Electron paramagnetic resonance and photo-electron paramagnetic resonance investigation on the recharging of the substitutional nitrogen acceptor in ZnO - Stehr, J. E.; Hofmann, D. M.; Meyer, B. K.; Justus Liebig University Giessen (My University, 2012)
We investigated the substitutional nitrogen center in ZnO single crystals by electron paramagnetic resonance (EPR) and photo-EPR spectroscopy. Aside the three principle hyperfine lines due to the interaction of the N0 (2p5) electron spin with the nitrogen nucleus (I=1, natural abundance 99.6%), we identify additional satellite lines which arise from delta mS=±1 and delta mI=±1, ±2 transitions becoming allowed due to quadrupole interaction. The quadrupole coupling constant e2qQ/h is determined to -5.9MHz with an asymmetry parameter of eta=0.05. These values are somewhat different from those obtained for the nitrogen center in ZnO powders, but are closer to the theoretical calculations of Gallino et al. We further carefully investigated the photon induced recharging of the N centers. We determine the energy hu required for the process NO-+hu -> NO0+ecb- to 2.1±0.05eV, the dependence of the EPR signal intensity on the illumination time shows a mono-exponential behavior which gives evidence that a direct ionization process is monitored.
Keywords: ddc:530